2003
DOI: 10.1046/j.1365-2672.2003.01988.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of antibiotic resistance between commensal and pathogenic members of the Enterobacteriaceae under ileal conditions

Abstract: Aim: To determine the rate of antibiotic resistance transmission between commensal and pathogenic representatives of the Enterobacteriaceae. Methods and Results: Through the use of a validated in vitro simulation of the porcine ileum, the transmission of antibiotic resistance was detected between commensal Escherichia coli, E. coli O157 and Salmonella spp. Countable transconjugant populations arose readily and, in one example, proved capable of indefinite persistence. Conclusions: Genetic material conferring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 32 publications
1
98
0
2
Order By: Relevance
“…Verotoxigenic E. coli strains were also identified within this cohort over the same period (35), and studies to examine whether these pathogens will accept resis-tance plasmids isolated from the commensal population are ongoing. Transmission of multiple-resistance phenotypes between epidemiologically unrelated commensal and pathogenic E. coli strains has recently been demonstrated in vitro under ileal conditions (7).…”
Section: Discussionmentioning
confidence: 99%
“…Verotoxigenic E. coli strains were also identified within this cohort over the same period (35), and studies to examine whether these pathogens will accept resis-tance plasmids isolated from the commensal population are ongoing. Transmission of multiple-resistance phenotypes between epidemiologically unrelated commensal and pathogenic E. coli strains has recently been demonstrated in vitro under ileal conditions (7).…”
Section: Discussionmentioning
confidence: 99%
“…The primer pairs 5ЈCATGGCGTCAAAAAGG3Ј and 5ЈTGCAAGAACCTCC TC3Ј amplified a 434-bp region of the rl4 gene. The 50-l reaction mixture in the setup for reverse transcription-PCR (RT-PCR) contained 25 l of 2Ï« SuperScript one-step RT-PCR buffer (a buffer containing 0.4 mM of each deoxynucleoside triphosphate and 2.4 mM MgSO 4 [Invitrogen]), 0.2 M of each of the four primers, 1 l of SuperScript II RT/Platinum Taq mix (Invitrogen), and 5 l of the treated RNA sample. The RT-PCR cycling conditions and product gel electrophoresis were according to standard procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Use of commensal organisms is convenient and allows measurement of the resistance gene pool that may be transmitted to pathogenic bacteria. Several studies have indicated that interspecies resistance transfer occur in bacteria, and increased recovery of antimicrobial resistant faecal E. coli was seen in dairy farms affected with resistant salmonellosis [6,8,11]. The level of resistance in commensal enteric bacteria has been correlated with resistance in pathogenic bacteria [11].…”
Section: Introductionmentioning
confidence: 99%